2019
DOI: 10.1177/0954405419883053
|View full text |Cite
|
Sign up to set email alerts
|

Residual stresses and strains analysis in press-braking bending parts considering multi-step forming effect

Abstract: Press-braking bending is a multi-step bending process and widely applied in the aerospace industry. Residual stresses and strains generated during the forming process play an important role in determining its forming parameters and bending path. This work aims to analyze the residual stresses and strains in press-braking bending parts using both the theoretical method and numerical method. First, the analytical model of residual stress and strain is established based on the elastic–plastic bending theory. Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…For single-pass bending process, the initial shape of the specimen is flat before loading. The analytical model of tangential stress (σθ) and residual stress ( σ θ res ) in the plastic deformation zone during one-step pressbrake forming are expressed as follows, which have been derived detailed in our former study 29 :…”
Section: Analysis Of Initial Bending Residual Stresses For Multi-step...mentioning
confidence: 99%
See 1 more Smart Citation
“…For single-pass bending process, the initial shape of the specimen is flat before loading. The analytical model of tangential stress (σθ) and residual stress ( σ θ res ) in the plastic deformation zone during one-step pressbrake forming are expressed as follows, which have been derived detailed in our former study 29 :…”
Section: Analysis Of Initial Bending Residual Stresses For Multi-step...mentioning
confidence: 99%
“…The FE algorithms and criterions to simulate the multi-step press-braking bending process along the specimen’s length direction has been summarized in our preliminary study. 29 The FE simulation process of multi-pass press bending at the same contact point between the indenter and specimen is shown in Figure 5. In order to reposition the indenter and supporter for the next-pass bending to prevent interference with the specimen, it is noted that coordinate transformations are adopted to obtain specifically values of translation distance or rotation angle.…”
Section: Numerical Analysis Of Multi-step Pressbrake Formingmentioning
confidence: 99%
“…The FSB is a forming method in which the whole die is discretized into several roller dies which can be adjusted independently at different positions, so as to form different target shapes. 1622 This forming method can be used for multiple purposes with one machine, reducing production costs, and improving production efficiency. Figure 1 is the schematic diagram of the overall die stretch bending forming and multi-point die stretch bending forming.…”
Section: The Fsb Processmentioning
confidence: 99%
“…Quadrini, Santo 25 have experimented with aluminum alloy material and reported that high hardness rubber gives the best surface finish. Some authors 2631 studied stamping operation, tool wear, single-point incremental forming, hydro-forming process with rubber tool by varying process parameters like compression ratio and speed and hot stamping process, multi-step forming reported that springback is less than the conventional process. From the literature review of conventional methods, it could be inferred that control of springback was attempted by analyzing the effect of various metal forming parameters, residual stresses, temperature, and friction.…”
Section: Introductionmentioning
confidence: 99%